2012
DOI: 10.1093/reseval/rvs001
|View full text |Cite
|
Sign up to set email alerts
|

Conservatism and risk-taking in peer review: Emerging ERC practices

Abstract: This article explores the newly founded European Research Council's (ERC) peer review system and its ability to sustain its mission to promote excellent, groundbreaking research. The article explores the extent to which the selection of groundbreaking research is constrained by inherent limitations in peer review by analysing the informal practices of ERC peer reviewers. This article notes that controversy and uncertainty are central characteristics of potentially groundbreaking research proposals. The selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 9 publications
3
136
0
Order By: Relevance
“…Some have suggested that highly innovative research may be associated with more reviewer uncertainty about their judgments of the methodology, which may lead to lower scores (Luukkonen 2012;Boudreau et al 2016). While reviewers may consider innovation in their decisions, they likely give this less weight than methodological weaknesses, which is reflected in the content of the reviewer's critique.…”
Section: Attitudes Toward Innovation and Riskmentioning
confidence: 99%
“…Some have suggested that highly innovative research may be associated with more reviewer uncertainty about their judgments of the methodology, which may lead to lower scores (Luukkonen 2012;Boudreau et al 2016). While reviewers may consider innovation in their decisions, they likely give this less weight than methodological weaknesses, which is reflected in the content of the reviewer's critique.…”
Section: Attitudes Toward Innovation and Riskmentioning
confidence: 99%
“…Scholarly interest in funding agencies ceased before interesting variations in their relative autonomy from the state and scientific communities (Braun 1998) or field-specific effects on the behaviour of researchers (Morris 2000) were fully investigated and theorised. Attention shifted to the study of funding programmes (Aguilar et al 1998;Melin and Danell 2006;Heinze 2008;Edler et al 2014), and here mostly to selection processes (Bornmann and Daniel 2005;Lamont 2009;Luukkonen 2012). This move has certainly been promoted by the growing interest of funders in the efficacy of their funding schemes and the commissioning of evaluation reports (Hornbostel et al 2009;Thomas and Nedeva 2012;M枚ller et al 2016).…”
Section: Targeting Changes In the Funding Of Sciencementioning
confidence: 99%
“…Including innovation specifically as one of the assessment criteria is another approach, aiming to actively change the way reviewers consider proposals (Lindner et al 2016;Luukkonen 2012). Views of the use of innovation as an assessment criterion have been mixed, with some suggesting that panels are not well placed to assess innovation because the expertise required is often lacking (Costello 2010), whilst others suggest that the approach is effective in rewarding innovation (Spiegel 2010).…”
Section: Alternative Approaches That May Help Foster Innovative Researchmentioning
confidence: 99%